2021
DOI: 10.3390/met11010107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Parameters on Interphase Precipitation and Mechanical Properties in Novel CrVNb Microalloyed Steel

Abstract: Novel steel microalloyed with 0.73 (Cr + V + Nb) has been subjected to thermomechanical processing (TMP) with varying parameters to simultaneously maximise the steel strength and ductility. Optical and electron microscopy studies coupled with uniaxial tensile testing were carried out to analyse the processing-microstructure-properties relationship. For the suggested steel composition, the simultaneously highest yield stress (960 MPa), ultimate tensile strength (1100 MPa), and elongation to failure (25%) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…For the current study, it can be speculated that HRS High V steel exhibits lower work hardening at the early stage of plastic deformation. Kostryzhev et al [ 71 ] have shown the relation between higher strength and lower work hardening rate of same steel processed under different conditions (finishing rolling temperature 900 °C, simulated coiling temperature 650 °C, and holding time 1800 s).…”
Section: Discussionmentioning
confidence: 99%
“…For the current study, it can be speculated that HRS High V steel exhibits lower work hardening at the early stage of plastic deformation. Kostryzhev et al [ 71 ] have shown the relation between higher strength and lower work hardening rate of same steel processed under different conditions (finishing rolling temperature 900 °C, simulated coiling temperature 650 °C, and holding time 1800 s).…”
Section: Discussionmentioning
confidence: 99%